Influence of body hair removal on physiological responses during breaststroke swimming - Sharp, R. L.; Costill, D. L. (Medicine & Science in Sports & Exercise, 1989)
The effects of body hair shaving on breaststroke performance were studied in nine shaved and four non-shaved swimmers prior to and after a conference swim meet. Distance per stroke, VO2max, heart rate, and blood lactate concentration were measured during a 400 yd breaststroke swim at 90% effort, and in three levels of tethered swimming. The shaved group showed significant blood lactate and VO2max reductions, while stroke length was increased for the 400 yd swim. The non-shaved swimmers demonstrated no changes. For tethered swimming, there were no significant changes for either group. Implication: Shaving body hair decreases the physiological effort for a set swim but does not alter strength or the ability to generate force. The benefits from shaving were considered to be due to reduction in active drag (which in turn reduces the physiological cost of swimming).